Starategi Manajemen Kepala Sekolah untuk Meningkatkan Kualitas Pembelajaran (Madrasah Aliyah) di Pondok Pesantren Persis 67 Kota Tasikmalaya - Irpan Irpan (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the principal’s management in improving the quality of students at Madrasah Aliyah Pesantren Persis Benda, Tasikmalaya. A descriptive qualitative method was employed with the principal, teachers, and administrative staff serving as informants. Data were collected through observation, interviews, and documentation. The findings indicate that the principal has carried out managerial functions effectively, including planning work programs, organizing teachers and staff, as well as implementing and supervising academic and administrative activities. The principal’s efforts in addressing obstacles also contribute to improving the quality of education. In conclusion, well-planned, well-organized, and well-supervised management by the principal plays a significant role in enhancing the educational quality of the madrasah. Keywords: management, principal, education quality